The Divine Conjectures: A Contemporary Account of Human Origins and Destiny - Russell, Allan Melvin (Zygon, 2008)
Abstract. Six “divine conjectures” frame the place of Theóne (The One to Whom we pray) in the creation of our universe and for its continuing development in five subsequent stages into a loving universe. The first stage, the cosmological universe, establishes the laws of nature, understood by scientists as the “standard model”. The second stage introduces life and death into the universe by a process we are only now beginning to understand. Stage 3 requires certain life forms to become conscious with a subset of those life-forms acquiring language that results in that subset becoming self-conscious. The next stage, Conjecture 4, identifies certain persons who become addicted to learning in their unrelenting effort to learn as much of what can be known as possible. The fifth conjecture requires individual persons to act as agents of Theóne in achieving Conjecture 6—a universe that is both loving and lawful. During the course of the exposition subsidiary discussions of the concepts of conjecture and hypothesis explicate the function of each in the advancement of knowledge and understanding. There are brief discussions of prayer and purpose in relation to the Divine.